Relationship between plaque composition by virtual histology intravascular ultrasound and clinical outcomes after percutaneous coronary intervention in saphenous vein graft disease patients: study protocol of a prospective cohort study - Yin Liu (BMC Cardiovascular Disorders, 2018)
Abstract Background Plaque composition and morphologic characteristics identified by virtual histology intravascular ultrasound (VH-IVUS) can determine plaques at increased risk of clinical events following percutaneous coronary intervention (PCI) among coronary artery disease (CAD) patients. However, there have been few studies to investigate the relationship between plaque composition of saphenous vein graft (SVG) by VH-IVUS and clinical outcomes in patients with saphenous vein graft disease (SVGD) undergoing PCI. The purpose of this study is to determine whether plaque components and characteristics by VH-IVUS can predict major adverse cardiac events (MACEs) among SVGD patients undergoing PCI. Methods/design This is a prospective cohort study conducted in Tianjin Chest Hospital, China. Participants with SVGD referred for PCI will be invited to participate in this study, and will be followed up at 1, 6, 12, 24 and 36 months post-PCI to assess clinical outcomes. The planned sample size is 175 subjects. We will recruit subjects with SVGD scheduled to receive PCI, aged 18–80 years, with a history of previous coronary artery bypass graft (CABG) surgery more than 1 year ago, and willing to participate in the study and sign informed consent. The composite primary study endpoint is the incidence of MACEs after PCI for SVGD, including death from cardiac causes, non-fatal myocardial infarction, unplanned target lesion revascularization (TLR) and target vessel revascularization (TVR). The primary outcome analysis will be presented as Kaplan-Meier estimates and the primary outcome analysis will be carried out using a Cox proportional hazards regression model. Discussion Once the predictive values of plaque components and characteristics by VH-IVUS on subsequent clinical outcomes are determined among SVGD patients undergoing PCI, an innovative prediction tool of clinical outcomes for SVGD patients undergoing PCI will be created, which may lead to the development of new methods of risk stratification and intervention guidance. Trial registration The study is registered to ClinicalTrials.gov (NCT03175952).